2022
DOI: 10.1111/add.15858
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal smoking, alcohol and caffeine exposure and offspring externalizing disorders: a systematic review and meta‐analysis

Abstract: Background and aims Several studies have indicated an association between maternal prenatal substance use and offspring externalizing disorders; however, it is uncertain whether this relationship is causal. We conducted a systematic review to determine: (1) if the literature supports a causal role of maternal prenatal substance use on offspring externalizing disorders diagnosis and (2) whether these associations differ across externalizing disorders. Methods We searched Web of Science, Embase, PsycINFO and Med… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…In addition, several confounders doubled the likelihood of ADHD in the child, including single parenthood and low disposable income. The reason that single parenthood doubles the likelihood of offspring ADHD is unknown, but may be related to the fact that low disposable family income is known to be more common among single parents, and an association between parental low disposable income and offspring ADHD is found in previous studies [ 25 , 26 ]. In addition, we found that reported smoking during pregnancy is associated with offspring ADHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several confounders doubled the likelihood of ADHD in the child, including single parenthood and low disposable income. The reason that single parenthood doubles the likelihood of offspring ADHD is unknown, but may be related to the fact that low disposable family income is known to be more common among single parents, and an association between parental low disposable income and offspring ADHD is found in previous studies [ 25 , 26 ]. In addition, we found that reported smoking during pregnancy is associated with offspring ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that reported smoking during pregnancy is associated with offspring ADHD. However, sibling- and twin-designed studies have shown that the association between smoking during pregnancy and ADHD is likely due to confounding because smoking during pregnancy is associated with ADHD/externalizing problems in the mother [ 25 ]. We therefore conclude that smoking during pregnancy is a confounding factor in our study as well.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the divergence noted above for BMI, this may be attributable to differences in sample size and caffeine groupings (i.e., our study grouping 2 or more cups into multigroup exposure and Zhang et al using a definition of 3 or more cups). There is a mixed literature surrounding associations between prenatal caffeine exposure and childhood externalizing with the majority of studies finding no evidence of association 35 , 38 . Notably, like a prior report arising from the ABCD Study finding 14 , our study revealed that daily and daily multiple cup prenatal caffeine exposure were nominally significantly associated with higher externalizing problems, but were not robust to multiple testing correction.…”
Section: Discussionmentioning
confidence: 99%
“…Child/Adolescent Behavior Problems. Associations between prenatal caffeine exposure and childhood behavioral outcomes have been less studied than BMI and have resulted in an equivocal literature 35,36 . Among child behavior problems examined, we found evidence for elevated sleep problems among children who were prenatally exposed to multiple cups daily.…”
Section: Bmimentioning
confidence: 99%
“…Current safety guidelines recommend a regular consumption of caffeine up to 200 mg/day, which is considered safe for the fetus [46]. Generally, low to moderate caffeine consumption during pregnancy has not been linked to attention-hyperactivity problems in offspring [8,34,[47][48][49]. The recommended upper limit for coffee consumption is between 300-384 mg/day, which is equivalent to three to four and a half cups of coffee per day [8,46,48].…”
Section: The Relationship Between Coffee Consumption and Adhdmentioning
confidence: 99%